2018
DOI: 10.1007/s00127-018-1599-6
|View full text |Cite|
|
Sign up to set email alerts
|

Girls get by with a little help from their friends: gender differences in protective effects of social support for psychotic phenomena amongst poly-victimised adolescents

Abstract: Purpose: To investigate whether social support is protective for psychotic experiences similarly among poly-victimised adolescent girls and boys. Methods: We utilised data from the Environmental Risk (E-Risk) Longitudinal Twin Study, a nationally-representative sample of 2,232 UK-born twins. Participants were privately interviewed at age 18 about victimisation, psychotic experiences, and social support during adolescence. Results: Perceived social support (overall and from friends) was found to be protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For example, Adewuya et al ( 62 ) has established a significant association between physical punishments at home and PLEs with an odd ratio of 1.98. Crush et al ( 63 ) also indicated that the positive effect of low level of family support on the occurrence of PLEs. We have also identified a negative association between school climate and PLEs, which also consolidates the findings in a study by Liu et al ( 64 ), who demonstrated that poor teacher-student relationship negatively predicted poor psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Adewuya et al ( 62 ) has established a significant association between physical punishments at home and PLEs with an odd ratio of 1.98. Crush et al ( 63 ) also indicated that the positive effect of low level of family support on the occurrence of PLEs. We have also identified a negative association between school climate and PLEs, which also consolidates the findings in a study by Liu et al ( 64 ), who demonstrated that poor teacher-student relationship negatively predicted poor psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[H2] Social factors Social factors are strongly linked with mental health 224 . Greater social support is related to reduced psychotic experiences in young adults with significant psychosis risk factors 124,223,[225][226][227] , and to reduced symptom severity 203,228,229 and improved functioning 229 in people diagnosed with a psychotic disorder. A meta-analysis further indicates that family interventions aimed at improving family support are associated with reduced relapse rates 216 .…”
Section: [H3] Abilitiesmentioning
confidence: 99%
“…and in individuals at high risk for psychosis 340 Greater social support is related to reduced psychotic experiences in young adults with significant psychosis risk 124,223,[225][226][227] , and to reduced symptom severity 203,228,229 and improved functioning 229 in people diagnosed with a psychotic disorder.…”
Section: Abilitiesmentioning
confidence: 99%
“…A wide variety of factors have been shown to be associated with psychotic experiences, including lower IQ (Cannon et al, 2002; Johns et al, 2004), adversity (Croft et al, 2019; Crush, Arseneault, & Fisher, 2018; McGrath et al, 2017; Morgan et al, 2014; Newbury et al, 2018; Oh, Cogburn, Anglin, Lukens, & DeVylder, 2016), poorer coping skills (Lin et al, 2011; Wigman et al, 2014a), migration (Laurens, West, Murray, & Hodgins, 2008; Scott et al, 2006), ethnicity (El Bouhaddani, van Domburgh, Schaefer, Doreleijers, & Veling, 2019; Oh, Yang, Anglin, & DeVylder, 2014) and socioeconomic factors (Scott et al, 2006), as well as genetic and molecular variation (Niculescu et al, 2015; Pain et al, 2018; Ramsay et al, 2013).…”
Section: Introductionmentioning
confidence: 99%